Method for additive manufacturing of stainless steel by adopting metal ceramic matrix

Through the method of additively manufacturing stainless steel in metal cermet matrix, the problems of high forming complexity, poor thermal conductivity and long processing cycle in traditional technology are solved, and high-quality and low-cost production results are achieved.

CN119634747AActive Publication Date: 2025-03-18SHENYANG JINFENG SPECIAL EQUIP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510175247.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

Traditional cermet matrix additive manufacturing technology faces problems such as high forming complexity, poor thermal conductivity, and long processing cycle when preparing complex structural parts, resulting in high manufacturing costs, poor product quality and performance.

Method used

The method of adding stainless steel to the metal cermet matrix is ​​adopted to prepare high-quality metal cermet wire through the mixing of scale graphite and concentrated acid solution, hot isostatic pressure treatment, hot extrusion treatment, and hot drawing treatment. The stainless steel powder is laid layer by layer through 3D printing technology, and finally sintering is performed in the sintering furnace to form a high-performance finished product.

Benefits of technology

It has achieved the accuracy of dimensionality, smooth surface, hardness and wear resistance of 3D finished products, solved the problems of insufficient quality and performance of finished products in traditional technology, and reduced production costs and cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of 3D printing manufacturing, discloses a method for additive manufacturing of stainless steel through a metal ceramic matrix, and aims at solving the problem that a traditional metal ceramic matrix composite material possibly has the defects in the aspects of hardness, abrasion resistance and corrosion resistance. Treating again to obtain turbid liquid; mixing the cooled turbid liquid after the reaction with an ethanol intercalation solvent for reaction, and performing ultrasonic treatment to obtain an intercalation solution; putting diethanol amine and the intercalation solution into a high-pressure reaction kettle for treatment, and finally performing suction filtration, water washing and drying to obtain nitrogen-doped graphene; titanium carbide, sulfonylated silicon carbide and nitrogen-doped graphene are put into a mixing machine according to different proportions to be premixed, composite powder is obtained and used for the additive stainless steel manufacturing process, a metal ceramic matrix additive manufacturing stainless steel method is adopted, the prepared 3D finished product is accurate in size, the quality of the finished product is improved, the surface is smooth and flawless, and the product quality is improved. And the hardness and the wear resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of 3D printing manufacturing, and specifically relates to a method for additively manufacturing stainless steel by using a metal ceramic matrix. Background Art

[0002] Cermets are composite materials composed of a ceramic hard phase and a metal or alloy bonding phase. Cermets are widely used in wear-resistant parts such as cutting tools. Additive manufacturing technology (also known as 3D printing) is a type of rapid prototyping technology. It is a technology based on digital model files, using powdered metal or plastic and other bondable materials to construct objects by stacking layer by layer. It is increasingly widely used in cutting tools, automobiles, aerospace, medical and other fields.

[0003] In the traditional tool and fixture manufacturing field, additive manufacturing of metal-ceramic matrix may face higher forming complexity. Especially for complex structural parts, more complex processes and more processing steps may be required to complete, which increases the manufacturing cost and cycle. In addition, the metal-ceramic matrix may have poor thermal conductivity, resulting in poor heat transfer inside the material, affecting the thermal stability and service life of the material. At the same time, poor thermal conductivity may also lead to difficulties in temperature control during processing, further affecting the quality and performance of the product. In addition, due to problems such as high forming complexity and poor thermal conductivity, the processing cycle of unimproved technology may be long. This not only increases production costs, but also may limit production efficiency and fail to meet the market's demand for rapid response and efficient production. The metal-ceramic matrix composites prepared by the original technology may have deficiencies in hardness, wear resistance and corrosion resistance. These performance deficiencies may cause the product to be easily damaged or fail during use, reducing the product's service life and reliability.

[0004] To solve the existing problems, we propose a method for additive manufacturing of stainless steel using a metal-ceramic matrix. Summary of the invention

[0005] The object of the present invention is to provide a method for additively manufacturing stainless steel using a metal ceramic matrix to solve the problems raised in the above background technology.

[0006] A method for additively manufacturing stainless steel using a metal ceramic matrix, the preparation steps comprising: S1: Mix flake graphite with concentrated acid solution in a mass ratio of 1:(110-140), stir at a temperature of 40-60°C, then add potassium permanganate and graphite in a mass ratio of (5-8):1, react at a temperature of 50-80°C for 6-7 hours, then heat to 70-100°C and react for 30-60 minutes to obtain a suspension; mix the cooled suspension with an ethanol intercalation solvent in a volume ratio of 22:(1-1.5) and ultrasonically treat to obtain an intercalation solution; put diethanolamine in a volume ratio of (1-5):100 and the intercalation solution into a high-pressure reactor, treat at a temperature of 190-220°C for 8-12 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene; S2: titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene are charged into a mixer in different proportions for premixing to obtain composite powder; S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed, and then the bag is placed in a hot isostatic press for hot isostatic pressing to form an ingot; S4: placing the ingot into a vacuum heat treatment furnace, and performing hot extrusion treatment on the ingot at 800-870° C. for 250-300 minutes to prepare an extruded wire; S5: drawing the extruded wire into a finished metal ceramic wire on a hot drawing device; S6: loading the metal ceramic wire prepared in S5 onto a plastic 3D printer, and printing out a metal ceramic green body according to a three-dimensional modeling program in a computer; S7: Stainless steel powder is placed on the surface of the metal ceramic substrate, and 35 to 50 layers are repeatedly laid using a 3D printer. After the printing is completed, a green embryo with stainless steel additives is obtained; S8: placing the green body after material addition into a sintering furnace with an inert protective gas, sintering at a temperature of 700 to 800°C and a holding time of 380 to 460 min, and then cooling the furnace to room temperature and taking it out after sintering; S9: Modify the surface of the finished product with a high-current pulsed electron beam, with an acceleration voltage of 20-25 kV, a pulse width of 2.5-3.5 μs, a pulse number of 5-25 times, and a target distance of 6-10 cm to obtain the finished product; The sulfonated silicon carbide in S2 includes the following groups: .

[0007] Preferably, the weight ratio of titanium carbide, sulfone-containing silicon carbide and nitrogen-doped graphene in S2 is (5-10): (2-6): (0.1-0.5).

[0008] Preferably, the hot isostatic pressing treatment parameters in S3 are a holding pressure of 90 to 150 MPa, a temperature of 850 to 870° C., and a holding time of 2 to 3 h.

[0009] Preferably, the hot extrusion process parameters in S4 are: an extrusion barrel temperature of 400-410° C., an extrusion barrel insulation time of 2-4 h, an extrusion pressure of 200-250 MPa, and an extrusion speed of 4-8 mm / s.

[0010] Preferably, the process parameters of the hot drawing in S5 are a current of 85 to 100 A and a wire drawing machine frequency of 3 to 5 Hz.

[0011] Preferably, the raw materials of the sulfonated silicon carbide include silicon carbide and 4,4'-dichlorodiphenyl sulfone.

[0012] Preferably, the preparation steps of the sulfonated silicon carbide include: T1: introducing ammonia into a device containing silicon carbide, reacting at a temperature of 1000-1300°C for 1-20 hours to obtain amino silicon carbide; T2: Dissolve 4,4'-dichlorodiphenyl sulfone with a solvent to obtain a solution, then add the catalyst and amino silicon carbide into the solution, react at a temperature of 80-150°C for 2-24 hours, and filter and dry to obtain sulfonated silicon carbide.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a metal ceramic matrix additive manufacturing stainless steel method, and the prepared 3D finished product has precise size, improved finished product quality, a smooth and flawless surface, and improved hardness and wear resistance. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] The present invention provides several technical solutions.

[0016] Embodiment 1:

[0017] Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1000°C for 1 hour to produce amino silicon carbide.

[0018] T2: Dissolve 20 parts of 4,4'-dichlorodiphenyl sulfone in dichlorobenzene to obtain a solution, then add 0.2 parts of cuprous chloride and amino silicon carbide into the solution, treat at 80°C for 2h, and filter and dry to obtain a solution with Sulfonylated silicon carbide with a group.

[0019] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated sulfuric acid solution in a mass ratio of 1:110, stir at a temperature of 40°C, add potassium permanganate and graphite in a mass ratio of 5:1 after stirring evenly, react at a temperature of 50°C for 6 hours, then heat to 70°C and react for 30 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 70% in a volume ratio of 22:1, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 190°C for 8 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0020] S2: titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene in a weight ratio of 5:2:0.1 are charged into a mixer for premixing to obtain a composite powder; S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 90 MPa, a temperature of 850 °C, and a holding time of 2 h.

[0021] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 800°C and a heat preservation time of 250 min, an extrusion barrel temperature of 400°C, an extrusion barrel heat preservation time of 2 h, an extrusion pressure of 200 MPa, and an extrusion speed of 4 mm / s to prepare an extruded wire.

[0022] S5: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 85 A and a drawing machine frequency of 3 Hz.

[0023] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0024] S7: Place stainless steel powder on the surface of the metal ceramic matrix, use a 3D printer, and repeat 35 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0025] S8: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 700°C for 380 min, and take it out after the furnace cools to room temperature after sintering.

[0026] S9: Use a high-current pulsed electron beam to modify the surface of the finished product, with an acceleration voltage of 20 kV, a pulse width of 2.5 μs, 5 pulses, and a target distance of 6 cm to obtain the finished product.

[0027] Embodiment 2:

[0028] Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1300°C for 20 hours to produce amino silicon carbide.

[0029] T2: Dissolve 30 parts of 4,4'-dichlorodiphenyl sulfone in dimethylformamide to obtain a solution, then add 1 part of aluminum chloride and amino silicon carbide to the solution, treat at 150°C for 24 hours, and filter and dry to obtain a Sulfonylated silicon carbide with a group.

[0030] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated nitric acid solution in a mass ratio of 1:140, stir at a temperature of 60°C, add potassium permanganate and graphite in a mass ratio of 8:1 after stirring evenly, react at a temperature of 80°C for 7 hours, then heat to 100°C and react for 60 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 95% in a volume ratio of 22:1.5, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 220°C for 12 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0031] S2: titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene in a weight ratio of 10:6:0.5 are charged into a mixer for premixing to obtain a composite powder; S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 150 MPa, a temperature of 870 °C, and a holding time of 3 h.

[0032] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 870°C and a heat preservation time of 300 min, an extrusion barrel temperature of 410°C, an extrusion barrel heat preservation time of 4 h, an extrusion pressure of 250 MPa, and an extrusion speed of 8 mm / s to prepare an extruded wire.

[0033] S5: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 100A and a drawing machine frequency of 5 Hz.

[0034] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0035] S7: Place stainless steel powder on the surface of the metal ceramic matrix, use a 3D printer, and repeat 50 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0036] S8: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 800 °C for 460 min, and take it out after the furnace cools to room temperature after sintering.

[0037] S9: The surface of the finished product is modified with a high-current pulsed electron beam, with an acceleration voltage of 25 kV, a pulse width of 3.5 μs, 25 pulses, and a target distance of 10 cm to obtain the finished product.

[0038] Embodiment 3:

[0039] Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1200°C for 10 hours to produce amino silicon carbide.

[0040] T2: Dissolve 25 parts of 4,4'-dichlorodiphenyl sulfone in xylene to obtain a solution, then add 0.5 parts of cuprous chloride and amino silicon carbide into the solution, treat at 100°C for 15 hours, and filter and dry to obtain Sulfonylated silicon carbide with a group.

[0041] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated sulfuric acid solution in a mass ratio of 1:120, stir at a temperature of 50°C, add potassium permanganate and graphite in a mass ratio of 7:1 after stirring evenly, react at a temperature of 70°C for 6.5 hours, then heat to 90°C and react for 50 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 90% in a volume ratio of 22:1.2, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 200°C for 10 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0042] S2: Titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene in a weight ratio of 6:3:0.3 are charged into a mixer for premixing to obtain composite powder.

[0043] S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 120 MPa, a temperature of 860 °C, and a holding time of 2.5 h.

[0044] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 830°C and a heat preservation time of 260 min, an extrusion barrel temperature of 405°C, an extrusion barrel heat preservation time of 3 h, an extrusion pressure of 230 MPa, and an extrusion speed of 6 mm / s to prepare an extruded wire.

[0045] S5: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 90 A and a drawing machine frequency of 4 Hz.

[0046] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0047] S7: Place stainless steel powder on the surface of the metal ceramic matrix, use a 3D printer, and repeat 40 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0048] S8: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 750 °C for 400 min, and take it out after the furnace cools to room temperature after sintering.

[0049] S9: Use a high-current pulsed electron beam to modify the surface of the finished product, with an acceleration voltage of 22 kV, a pulse width of 3 μs, 15 pulses, and a target distance of 8 cm to obtain the finished product.

[0050] Comparative Example 1: Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1200°C for 10 hours to produce amino silicon carbide.

[0051] T2: Dissolve 25 parts of 4,4'-dichlorodiphenyl sulfone in xylene to obtain a solution, then add 0.5 parts of cuprous chloride and amino silicon carbide into the solution, treat at 100°C for 15h, and filter and dry to obtain Sulfonylated silicon carbide with a group.

[0052] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated sulfuric acid solution in a mass ratio of 1:120, stir at a temperature of 50°C, add potassium permanganate and graphite in a mass ratio of 7:1 after stirring evenly, react at a temperature of 70°C for 6.5 hours, then heat to 90°C and react for 50 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 90% in a volume ratio of 22:1.2, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 200°C for 10 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0053] S2: Titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene in a weight ratio of 6:3:0.3 are charged into a mixer for premixing to obtain composite powder.

[0054] S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 120 MPa, a temperature of 860 °C, and a holding time of 2.5 h.

[0055] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 830°C and a heat preservation time of 260 min, an extrusion barrel temperature of 405°C, an extrusion barrel heat preservation time of 3 h, an extrusion pressure of 230 MPa, and an extrusion speed of 6 mm / s to prepare an extruded wire.

[0056] S5: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 90 A and a drawing machine frequency of 4 Hz.

[0057] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0058] S7: Place stainless steel powder on the surface of the metal ceramic matrix, use a 3D printer, and repeat 40 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0059] S8: The green body after material addition is placed in a sintering furnace with an inert protective gas, and kept at 750 °C for 400 min. After sintering, the furnace is cooled to room temperature and taken out to obtain a finished product.

[0060] Comparative Example 2: Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated sulfuric acid solution in a mass ratio of 1:120, stir at a temperature of 50°C, add potassium permanganate and graphite in a mass ratio of 7:1 after stirring evenly, react at a temperature of 70°C for 6.5 hours, then heat to 90°C and react for 50 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 90% in a volume ratio of 22:1.2, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 200°C for 10 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0061] S2: Titanium carbide, silicon carbide and nitrogen-doped graphene in a weight ratio of 6:3:0.3 are charged into a mixer for premixing to obtain composite powder.

[0062] S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 120 MPa, a temperature of 860 °C, and a holding time of 2.5 h.

[0063] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 830°C and a heat preservation time of 260 min, an extrusion barrel temperature of 405°C, an extrusion barrel heat preservation time of 3 h, an extrusion pressure of 230 MPa, and an extrusion speed of 6 mm / s to prepare an extruded wire.

[0064] S5: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 90 A and a drawing machine frequency of 4 Hz.

[0065] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0066] S7: Place stainless steel powder on the surface of the metal ceramic matrix and use a 3D printer to repeatedly lay 40 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0067] S8: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 750 °C for 400 min, and take it out after the furnace cools to room temperature after sintering.

[0068] S9: Use a high-current pulsed electron beam to modify the surface of the finished product, with an acceleration voltage of 22 kV, a pulse width of 3 μs, 15 pulses, and a target distance of 8 cm to obtain the finished product.

[0069] Comparative Example 3: Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1200°C for 10 hours to produce amino silicon carbide.

[0070] T2: Dissolve 25 parts of 2,5-dichlorodiphenyl sulfone in xylene to obtain a solution, then add 0.5 parts of cuprous chloride and amino silicon carbide into the solution, treat at 100°C for 15 hours, and obtain sulfonated silicon carbide after filtration and drying.

[0071] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Mix flake graphite and concentrated sulfuric acid solution in a mass ratio of 1:120, stir at a temperature of 50°C, add potassium permanganate and graphite in a mass ratio of 7:1 after stirring evenly, react at a temperature of 70°C for 6.5 hours, then heat to 90°C and react for 50 minutes to obtain a suspension; mix the cooled suspension after the reaction with an ethanol intercalation solvent with a concentration of 90% in a volume ratio of 22:1.2, and ultrasonically treat to obtain an intercalation solution; put diethanolamine and the intercalation solution into a high-pressure reactor, treat at a temperature of 200°C for 10 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene.

[0072] S2: Titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene in a weight ratio of 6:3:0.3 are charged into a mixer for premixing to obtain composite powder.

[0073] S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 120 MPa, a temperature of 860 °C, and a holding time of 2.5 h.

[0074] S4: placing the billet into a vacuum heat treatment furnace, performing hot extrusion treatment at a billet temperature of 830°C and a heat preservation time of 260 min, an extrusion barrel temperature of 405°C, an extrusion barrel heat preservation time of 3 h, an extrusion pressure of 230 MPa, and an extrusion speed of 6 mm / s to prepare an extruded wire.

[0075] S5: The extruded wire is drawn into a finished wire on a hot drawing device, and the drawing process parameters are a current of 90 A and a drawing machine frequency of 4 Hz.

[0076] S6: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to a three-dimensional modeling program in a computer.

[0077] S7: Place stainless steel powder on the surface of the metal ceramic matrix and use a 3D printer to repeatedly lay 40 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0078] S8: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 750 °C for 400 min, and take it out after the furnace cools to room temperature after sintering.

[0079] S9: Use a high-current pulsed electron beam to modify the surface of the finished product, with an acceleration voltage of 22 kV, a pulse width of 3 μs, 15 pulses, and a target distance of 8 cm to obtain the finished product.

[0080] Comparative Example 4: Preparation of sulfonated silicon carbide: T1: Ammonia gas is introduced into a device containing silicon carbide and treated at 1200°C for 10 hours to produce amino silicon carbide.

[0081] T2: Dissolve 25 parts of 4,4'-dichlorodiphenyl sulfone in xylene to obtain a solution, then add 0.5 parts of cuprous chloride and amino silicon carbide into the solution, treat at 100°C for 15h, and filter and dry to obtain Sulfonylated silicon carbide with a group.

[0082] Preparation of stainless steel for additive manufacturing with metal ceramic matrix: S1: Titanium carbide, sulfone-based silicon carbide and graphene in a weight ratio of 6:3:0.3 are charged into a mixer for premixing to obtain composite powder.

[0083] S2: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed. The bag is then placed in a hot isostatic press for hot isostatic pressing to form an ingot. The isostatic pressing parameters are a holding pressure of 120 MPa, a temperature of 860 °C, and a holding time of 2.5 h.

[0084] S3: The billet is placed in a vacuum heat treatment furnace, and hot extrusion treatment is performed at a billet temperature of 830°C and a heat preservation time of 260 min. The extrusion barrel temperature is 405°C, the extrusion barrel heat preservation time is 3 h, the extrusion pressure is 230 MPa, and the extrusion speed is 6 mm / s to prepare an extruded wire.

[0085] S4: The extruded wire is drawn into a finished metal ceramic wire on a hot drawing device, and the drawing process parameters are a current of 90 A and a drawing machine frequency of 4 Hz.

[0086] S5: The metal ceramic filament prepared in S5 is loaded onto a plastic 3D printer, and the metal ceramic green body is printed out according to the three-dimensional modeling program in the computer.

[0087] S6: Place stainless steel powder on the surface of the metal ceramic matrix and use a 3D printer to repeatedly lay 40 layers. After printing is completed, a green embryo with stainless steel additives is obtained.

[0088] S7: Place the green body after material addition into a sintering furnace with inert protective gas, keep it at 750 °C for 400 min, and take it out after the furnace cools to room temperature after sintering.

[0089] S8: The surface of the finished product is modified with a high-current pulsed electron beam, with an acceleration voltage of 22 kV, a pulse width of 3 μs, 15 pulses, and a target distance of 8 cm to obtain the finished product.

[0090] Observe the surface conditions of the finished products prepared in Examples 1-3 and Comparative Examples 1-4, and test the hardness and wear resistance of the finished products; Test the tensile strength, elongation and Young's modulus of extruded wire during the preparation of the finished product.

[0091] Table 1 Test results

[0092] From the comparison between Examples 1-3 and Comparative Example 1, it can be seen that the finished product prepared in Comparative Example 1 has a qualified size, but has a crack on the surface, and the hardness and wear resistance are significantly reduced.

[0093] From the comparison between Examples 1-3 and Comparative Example 2, it can be seen that the finished product prepared in Comparative Example 2 is unqualified in size, has 2 inward shrinkages, 2 burrs, and the hardness does not change much, but the wear resistance is significantly reduced. The tensile strength of the extruded wire in Comparative Example 2 does not change much, but the elongation is about 50% lower than that of Examples 1-3, and the Young's modulus is not much different.

[0094] From the comparison between Examples 1-3 and Comparative Example 3, it can be seen that the finished product prepared in Comparative Example 3 has qualified dimensions, but has one pore, poor surface condition, and little change in hardness and wear resistance. The tensile strength of the extruded wire in Comparative Example 3 is reduced by about 30%, the elongation is about 50% lower, and the Young's modulus does not change much.

[0095] From the comparison between Examples 1-3 and Comparative Example 4, it can be seen that the finished product prepared in Comparative Example 4 is unqualified in size, has 2 inward shrinkages, and has 3 pores, the surface condition is poor, the hardness and wear resistance do not change much, the tensile strength of the extruded wire in Comparative Example 4 is reduced by about 30%, the elongation is about 25% lower, and the Young's modulus does not change much.

[0096] Although embodiments of the present invention have been shown and described (see the above detailed description for details), it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for additively manufacturing stainless steel using a metal ceramic matrix, characterized in that: The preparation steps include: S1: Mix flake graphite with concentrated acid solution in a mass ratio of 1:(110-140), stir at a temperature of 40-60°C, then add potassium permanganate and graphite in a mass ratio of (5-8):1, react at a temperature of 50-80°C for 6-7 hours, then heat to 70-100°C and react for 30-60 minutes to obtain a suspension; mix the cooled suspension with an ethanol intercalation solvent in a volume ratio of 22:(1-1.5) and ultrasonically treat to obtain an intercalation solution; put diethanolamine in a volume ratio of (1-5):100 and the intercalation solution into a high-pressure reactor, treat at a temperature of 190-220°C for 8-12 hours, and finally filter, wash with water and dry to obtain nitrogen-doped graphene; S2: titanium carbide, sulfone-based silicon carbide and nitrogen-doped graphene are charged into a mixer in different proportions for premixing to obtain composite powder; S3: The composite powder is placed in a stainless steel bag, and the stainless steel bag is vacuumed, and then the bag is placed in a hot isostatic press for hot isostatic pressing to form an ingot; S4: placing the ingot into a vacuum heat treatment furnace, and performing hot extrusion treatment on the ingot at 800-870° C. for 250-300 minutes to prepare an extruded wire; S5: drawing the extruded wire into a finished metal ceramic wire on a hot drawing device; S6: loading the metal ceramic wire prepared in S5 onto a plastic 3D printer, and printing out a metal ceramic green body according to a three-dimensional modeling program in a computer; S7: Stainless steel powder is placed on the surface of the metal ceramic substrate, and 35 to 50 layers are repeatedly laid using a 3D printer. After the printing is completed, a green embryo with stainless steel additives is obtained; S8: placing the green body after material addition into a sintering furnace with an inert protective gas, sintering at a temperature of 700-800°C and a holding time of 380-460 min, and then cooling the furnace to room temperature and taking it out after sintering; S9: Modify the surface of the finished product with a high-current pulsed electron beam, with an acceleration voltage of 20-25 kV, a pulse width of 2.5-3.5 μs, a pulse number of 5-25 times, and a target distance of 6-10 cm to obtain the finished product; The sulfonated silicon carbide in S2 includes the group: 。 2. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 1, characterized in that: The weight ratio of titanium carbide, sulfone-containing silicon carbide and nitrogen-doped graphene in S2 is (5-10): (2-6): (0.1-0.5).

3. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 1, characterized in that: The hot isostatic pressing treatment parameters in S3 are: a holding pressure of 90 to 150 MPa, a temperature of 850 to 870° C., and a holding time of 2 to 3 h.

4. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 1, characterized in that: The hot extrusion process parameters in S4 are: extrusion barrel temperature of 400-410°C, extrusion barrel insulation time of 2-4 h, extrusion pressure of 200-250 MPa, and extrusion speed of 4-8 mm / s.

5. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 1, characterized in that: The process parameters of the hot drawing described in S5 are a current of 85 to 100 A and a wire drawing machine frequency of 3 to 5 Hz.

6. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 1, characterized in that: The raw materials of the sulfonated silicon carbide include silicon carbide and 4,4'-dichlorodiphenyl sulfone.

7. The method for additively manufacturing stainless steel using a metal ceramic matrix according to claim 6, characterized in that: The preparation steps of the sulfonated silicon carbide include: T1: introducing ammonia into a device containing silicon carbide, reacting at a temperature of 1000-1300°C for 1-20 hours to obtain amino silicon carbide; T2: Dissolve 4,4'-dichlorodiphenyl sulfone with a solvent to obtain a solution, then add the catalyst and amino silicon carbide into the solution, react at a temperature of 80-150°C for 2-24 hours, and filter and dry to obtain sulfonated silicon carbide.

Citation Information

Patent Citations

  • Preparation method of low-layer gauze-shaped nitrogen-doped graphene

    CN111591981A

  • Preparation method of nano ceramic powder reinforced wave-absorbing polyester fibers

    CN112267156A

  • Method for preparing metal ceramic part with complex shape based on spherical feed printing

    CN115351290A

  • MoCoB-Co metal ceramic selective laser melting additive manufacturing method

    CN117961087A

  • Novel electron beam gun for vacuum electron beam cladding of composite powder

    CN216706276U